Uses of Indexes and Data Bases for Information Releases Analysis. - Wright, Charlotte J.; Groff, James E. (The Accounting Review, 1986)
This study assesses the relative effectiveness of searches of the Wall Street Journal Index and Dialog data base searches for information release analyses. The results indicate that the Wall Street Journal Index is more effective than Dialog, but a substantial number of information events do not appear in either service. In addition, the Wall Street Journal Index searches found a large number of financial type announcements but found only about 35 percent of nonfinancial items, Stock price data are presented which indicate that items not appearing in the Wall Street Journal Index are as likely to occasion significant price reactions as items which do appear in the Index.